Decomposing the German East-West wage gap - Jan Kluge; Michael Weber (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2015)
We demonstrate that almost one half of the observed wage gap between East and WestGermany reflects differences in worker, establishment, and regional characteristicsrather than differences in productivity at the establishment level. Regional price andestablishment size differentials alone account for one quarter of the overall East-Westwage gap. Differences in employees' characteristics and in productivity deliver muchsmaller but still statistically significant contributions. We derive these results from anOaxaca-Blinder decomposition using unusually rich linked employer-employee data.Our findings are quite stable over the period from 1996 to 2010 and over the wagedistribution.
Keywords: J31; P25; R11; 330; Wage gap; decomposition; German reunification